Peningkatan Keterlibatan dan Prestasi Belajar Matematika Melalui Discovery Learning Bagi Siswa MTs Negeri 8 Kebumen - Wardani, Yulianti (Mulya Literasi Publishing, 2024)
This study aims to determine the application of the discovery learning model in improving the activeness and achievement of mathematics learning of MTs Negeri 8 Kebumen students. The research method used was Classroom Action Research. The results of this study indicate that the application of the discovery learning model can increase learning activeness. That is, the liveliness which initially amounted to 63.89%, after being applied or treated with this learning method increased to 94.44%. Not only that, the results of the application of the discovery learning model can also improve learning achievement which initially had an average of 65.61%, after implementing this method to 79.28% and learning completeness from 61.11% to 86.11%.